LINGUA-SEMANTIC ANALYSIS OF APHORISMS IN THE ENGLISH AND UZBEK LANGUAGES - Rustamova Durdona Muhammadsoli qizi (Western European Studies, 2024)
This article discusses the study of aphorisms that delves into the realm of semantic implications, transcending literal meanings to explore profound insights into language, societal norms, and human cognition. Aphorisms serve as intellectual repositories, encapsulating complex ideas in succinct and memorable phrases, offering insights into a culture's history, values, and worldview. This article examines the structural and semantic characteristics of aphorisms, emphasizing their role in conveying universal truths and facilitating cognitive organization
Keywords: Aphorism; Aphoristic; English aphorisms; Uzbek aphorisms